Corrigendum on “Isorhamnetin augments the anti-tumor effect of capeciatbine through the negative regulation of NF-κB signaling cascade in gastric cancer” [Cancer Lett. 363 (1) (2015) 28–36] - Manu, K.; Shanmugam, M.; Ramachandran, L.; Li, F.; Siveen, K.; Chinnathambi, A.; Zayed, M.; Alharbi, S.; Arfuso, Frank; Kumar, Alan Prem; Ahn, K.; Sethi, G. (Elsevier, 2018)
© 2018 The authors regret that there was a typographical error in the title of the article “Capeciatbine” should be spelled as “Capecitabine”. The authors would like to apologize for any inconvenience caused.